2021
DOI: 10.1016/j.wjorl.2021.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the risk of cerebrospinal fluid rhinorrhea following translabyrinthine surgery of the posterior fossa

Abstract: Objective To describe the procedure and results of an adapted closure and reconstruction technique for translabyrinthine surgery that focuses on identifying and managing potential pathways for CSF egress to the middle ear and Eustachian tube. Methods Retrospective review of a cohort of translabyrinthine acoustic neuroma cases that were reconstructed using this technique. Results In addition to meticulous packing of potential conduits using so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 12 publications
0
20
1
Order By: Relevance
“…Thirteen studies 15,20,21,28,[31][32][33][35][36][37][38][39]43 performed fat packing in isolation with no reported adjuncts. Some institutions [40][41][42] attempted to mitigate This article is protected by copyright. All rights reserved.…”
Section: Dural Phasementioning
confidence: 99%
See 4 more Smart Citations
“…Thirteen studies 15,20,21,28,[31][32][33][35][36][37][38][39]43 performed fat packing in isolation with no reported adjuncts. Some institutions [40][41][42] attempted to mitigate This article is protected by copyright. All rights reserved.…”
Section: Dural Phasementioning
confidence: 99%
“…Several studies reported an onlay technique to seal the dura, employing autologous grafts, xenografts and synthetic dural substitutes. 17,21,22,25,42,[47][48][49][50] Autologous onlays consisted of fascia grafts, harvested either from the abdomen or thigh. 17,22,25,42,48,51 Variations in the autologous onlay technique centred around the size of the graft used, ranging from slightly larger than the dural defect to a 'peri cranial graft basket' 47 .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations